LIBRARY ANXIETY MAHASISWA ASING DI PERPUSTAKAAN - Fatmawati, Riya; Rohyati Zulaikha, Sri (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2022)
Library anxiety is a unique phenomenon. Anxiety often arises when someone is in a new place. Padang State University has some students from several countries. Environmental and cultural differences force the students to adapt to their new environment. Anxiety could arise due to the lack of exposure in the library environment or lack of knowledge of the library. One of the anxious attitudes can be seen in the reluctance of students to come to the library. This study aims to determine library anxiety and the factors of library anxiety towards foreign students at the Padang State University Library using a descriptive method with a case study approach, Data collection was carried out using structured interview techniques, observation, and documentation. The informants in this study were five foreign students that selected based on purposive sampling. Research result shows that foreign students at Padang State University Library do not experience library anxiety. This can be seen from the results that from nine questions given, six questions were answered positively by the informants and just three questions confirmed negative: lack of knowledge about where, how to start, and library knowledge barriers.